SEJARAH PERKEMBANGAN PEMBELAJARAN BAHASA MELAYU DI JEPUN - Moriyama, Mikihiro (WILAYAH: The International Journal of East Asian Studies, 2023)
The Japanese started learning Malay at the end of the 19th century. The first Malay primer was published in the 1900s. A number of books and dictionaries of Malay were published thereafter exceeding 200 titles. The Japanese began to sail to the Southeast Asian region, especially the Malay peninsula and the Dutch East Indies’ islands after the Tokugwa Shogunate administration ended and Meiji period began in 1868. The Japanese moved to Nanyo (the southern regions) of Japan to seek their fortune as small shopkeepers, peddlers and some even became prostitutes. Japanese enterprises were stimulated by the so-called Nanshin Ron (Advance Southward Ideology), which prevailed in the 1920s and 1930s. They gradually operated rubber plantations and iron mine companies and other businesses as well. In terms of economic activities, it was necessary to learn the languages of the locals for business communications and business interests. They thought Malay was the most prominent communication tool among the many languages used in the southern regions. For this purpose, the Japanese began learning Malay in schools in Japan. The peak of Malay learning was the time of Japanese expansion policy based on militarism in the 1940s. The total number of publications of primer and dictionary reached more than 50 titles during this period. After the end of the Second World War, Malay language learning did not receive much attention in Japanese society but it changed when business interest in Southeast Asia became stimulated by government policy including war reparations. The article provides a rough sketch of Malay language learning in Japan in the first place and in the final part discusses how Japanese government and society have maintained and promoted their own language and identity as a policy to develop the nation and state in terms of language teaching in both foreign languages and national language.